Survey on the current status of syphilis infection and awareness of sexually transmitted diseases among pregnant and postpartum women - YUAN Yanyi; ZHANG Yinan; ZHAO Peizhen; HUANG Shujie; LI Zhuoying; QIU Yongjun (Pifu-xingbing zhenliaoxue zazhi)
[Objective] To assess the status of syphilis infection and knowledge of sexually transmitted diseases (STDs) among pregnant and postpartum women in Zhongshan city of Guangdong province, and to analyze the factors influencing their knowledge of STDs, providing scientific evidence for future targeted interventions. [Methods] Stratified sampling was used to recruit pregnant women who visited four medical institutions in Zhongshan city for the first time between 2023 and 2024 for pregnancy registration, prenatal care, or delivery. Syphilis serological tests were conducted, and data were collected through a questionnaire. The questionnaire covered general demographic characteristics, knowledge of STDs, behavioral information, and previous STD history. The data were analyzed using SPSS 26.0 software. [Results] A total of 800 pregnant and postpartum women were included, with a mean age of 29.37±5.31 years. The syphilis infection rate was 1.00%, while the awareness rate of STD knowledge was 55.63%. Higher levels of STD knowledge were associated with higher education (OR=2.113), gestational age less than 11 weeks at enrollment (OR=1.926), and a history of previous pregnancies (OR=1.750). [Conclusions] The syphilis infection rate among pregnant and postpartum women is still relatively high, and the awareness of sexually transmitted diseases is low, particularly among those with lower educational levels, gestational age beyond 11 weeks, and no history of previous pregnancies. Targeted STD health education should be provided to these populations to enhance their awareness of STD and self-protection.